2008
DOI: 10.2174/1874256400802010072
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Resistant Lactococcus lactis 1A-1 Isolated from a Competitive Exclusion Product Transfers Vancomycin Resistance Genes to Staphylococcus aureus

Abstract: A vancomycin-resistant Lactococcus lactis isolate 1A-1 from a competitive exclusion (CE) product contained plasmid-encoded vanA, B, C1, and C2/3 genes. The L. lactis 1A-1 conjugatively transferred the genes to Staphylococcus aureus in vitro. CE product bacteria may be reservoirs for dissemination of vanA, B, and C genes to the human gastrointestinal microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Therefore, based on morphological determinants, high-throughput sequencing, and PCR performed with specific primers, we concluded that the organism present in the feces of the antibiotic-treated mice was Lactococcus. This result is consistent with the findings presented by Dollive et al [36] However, Lactococcus is not a fastidious organism so it should have been readily cultivated, and although previous studies have identified vancomycin resistant strains of Lactococcus [53] an ampicillin resistant strain has not yet been identified.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, based on morphological determinants, high-throughput sequencing, and PCR performed with specific primers, we concluded that the organism present in the feces of the antibiotic-treated mice was Lactococcus. This result is consistent with the findings presented by Dollive et al [36] However, Lactococcus is not a fastidious organism so it should have been readily cultivated, and although previous studies have identified vancomycin resistant strains of Lactococcus [53] an ampicillin resistant strain has not yet been identified.…”
Section: Discussionsupporting
confidence: 92%
“…The differences in the sequencing analysis between the V3 and V4 ( [53][54][55] , and follow-up testing on the isolates from the fecal samples from the antibiotic-treated mice found the Enterococcus strain to be resistant to vancomycin and intermediate to ampicillin (data not shown). Thus we were forced to resolve the seemingly incongruous dilemma of whether the organism that is observed by Gram-stain and flow cytometry is Lactococcus or Enterococcus, and if it was Lactococcus why did it not grow in culture.…”
Section: Discussionmentioning
confidence: 99%